Floral architecture, breeding system, seed biology and chromosomal studies in endangered Himalayan Angelica glauca Edgew. (Apiaceae) - Kamini Gautam; Ravinder Raina (Caryologia, 2019)
Endangered Angelica glauca an important medicinal plant of temperate Himalaya is valued for its roots which are used to treat several diseases besides food flavouring. Reproductive biology studies conducted in this species for the first time have revealed i). presence of umbels of different orders with only bisexual flowers ii). occurrence of sterile seeds (without embryo) apart from fertile ones iii). seed set in only early blooming umbels (primary and lateral-I) iv). 2n=22 chromosomes besides presence of chromosomes in a group at metaphase and anaphase-I and cytomixis in some pollen mother cells and v). extreme protoandry and cross pollination behavior (upto 95%) of the species. These observations have implications for developing any conservation plan for the species.